Comparative genomic of metabolic and reaction in cyanobacteria models [electronic resource] - Siti Haryani Anuar, 1992-; Afnizanfaizal Abdullah, supervisor; Fakulti Komputeran (2015)
Project Paper (Sarjana Muda Sains Komputer (Bioinformatik)) - Universiti Teknologi Malaysia, 2015